SensAct: The Soft and Squishy Tactile Sensor with Integrated Flexible Actuator. (21st January 2021) - Ozioko, Oliver; Karipoth, Prakash; Escobedo, Pablo; Ntagios, Markellos; Pullanchiyodan, Abhilash; Dahiya, Ravinder
Abstract : Herein, a novel tactile sensing device (SensAct) with a soft touch/pressure sensor seamlessly integrated on a flexible actuator is presented. The squishy touch sensor is developed with custom‐made graphite paste on a tiny permanent magnet, encapsulated in Sil‐Poxy, and the actuator (15 μ‐thick coil) is fabricated on polyimide by Lithographie Galvanoformung Abformung (LIGA) micromolding method. The actuator can operate in two modes (expansion and contraction/squeeze) and two states (vibration and nonvibration). The sensor was tested with up to 12 N applied forces and exhibited ≈70% average relative resistance variation (Δ R / R o ), ≈0.346 kPa −1 sensitivity, and ≈49 ms response time with excellent repeatability (≈12.7% coefficient of variation) at 5 N. During simultaneous sensing and actuation, the modulation of coil current, due to Δ R / R o (≈14% at 2 N force) in the sensor, allows the close loop control (Δ I / I o ≈385%) of expansion/contraction (≈69.8 μm expansion in nonvibration state and ≈111.5 μm peak‐to‐peak in the vibration state). Finally, the soft sensor is embedded in the 3D‐printed fingertip of a robotic hand to demonstrate its use for pressure mapping along with remote vibrotactile stimulation using SensAct device. The self‐controllable actuation of SensAct could provide eSkin the ability to tune stiffness and the vibration states could be utilized for controlled haptic feedback. Abstract : Herein, a novel tactile sensing device (SensAct) with soft piezoresistive pressure sensor seamlessly integrated on a flexible electromagnetic actuator to allow simultaneous tactile sensing and actuation for haptic interaction is presented. The integrated actuator can operate in two modes (expansion and contraction) and two states (vibration and nonvibration). SensAct is applicable in eSkin with tunable properties and localizes vibrotactile feedback.